Risk Factors for Stillbirth among Pregnant Women Infected with Syphilis in the Zhejiang Province of China, 2010–2016 - Cui-Cui Duan; Xiao-Hui Zhang; Shan-Shan Li; Wei Wu; Li-Qian Qiu; Jian Xu (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. The World Health Organization estimated that about 1.36 million pregnant women suffered from syphilis in 2008, and nearly 66% of adverse effects occurred in those who were not tested or treated. Syphilis infection is one of the most common maternal factors associated with stillbirth. Objective. This study aimed to determine the risk factors for stillbirth among pregnant women infected with syphilis. Methods. In this retrospective study, data on stillbirth and gestational syphilis from 2010 to 2016 were extracted from the prevention of mother-to-child transmission (PMTCT) program database in the Zhejiang province. A total of 8,724 pregnant women infected with syphilis were included. Multiple logistic regression analysis was performed to determine the degree of association between gestational syphilis and stillbirth. Results. We found that the stillbirth percentage among pregnant women infected with syphilis was 1.7% (152/8,724). Compared with live births, stillbirth was significantly associated with lower maternal age, not being married, lower gravidity, the history of syphilis, nonlatent syphilis stage, higher maternal serum titer for syphilis, inadequate treatment for syphilis, and later first antenatal care visit. In multiple logistic analysis, nonlatent syphilis (adjusted odds ratio (AOR) = 2.03; 95% CI = 1.17, 3.53) and maternal titers over 1 : 4 (AOR = 1.78; 95% CI = 1.25, 2.53) were risk factors for stillbirth, and adequate treatment was the only protective factor for stillbirth (AOR = 0.16; 95% CI = 0.10, 0.25). Conclusions. Nonlatent syphilis and maternal titers over 1 : 4 were risk factors for stillbirth, and adequate treatment was the only protective factor for stillbirth.